2003
DOI: 10.1074/jbc.m303547200
|View full text |Cite
|
Sign up to set email alerts
|

Alzheimer β-Amyloid Homodimers Facilitate Aβ Fibrillization and the Generation of Conformational Antibodies

Abstract: We reported previously that stabilized ␤-amyloid peptide dimers were derived from mutant amyloid precursor protein with a single cysteine in the ectodomain juxtamembrane position. In vivo studies revealed that two forms of SDS-stable A␤ homodimers exist, species ending at A␤40 and A␤42. The phenomenon of the transformation of the initially deposited 42-residue ␤-amyloid peptide into the amyloid fibrils of Alzheimer's disease plaques remains to be explained in physical terms, i.e. energetically and structurally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
76
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(81 citation statements)
references
References 44 publications
3
76
2
Order By: Relevance
“…We have previously reported similar results where large sizes of particles formed with N-terminal modification of RRAA-KLVFF compared to C-terminal modification using six oligolysine chains (25). The particle size difference is closely Article associated with the disruption of the hydrophobic C-terminal group (50), which has more impact on aggregation than the hydrophilic N-terminal (51). The different morphologies of particles formed with AAMP-19 (fibrils) and AAMP-16 (spherical aggregates) are attributable of the N-and C-terminal modifications, respectively.…”
Section: Size and Morphology Of Structures Formed By The Disassembly supporting
confidence: 59%
“…We have previously reported similar results where large sizes of particles formed with N-terminal modification of RRAA-KLVFF compared to C-terminal modification using six oligolysine chains (25). The particle size difference is closely Article associated with the disruption of the hydrophobic C-terminal group (50), which has more impact on aggregation than the hydrophilic N-terminal (51). The different morphologies of particles formed with AAMP-19 (fibrils) and AAMP-16 (spherical aggregates) are attributable of the N-and C-terminal modifications, respectively.…”
Section: Size and Morphology Of Structures Formed By The Disassembly supporting
confidence: 59%
“…21 and 29. Aβ42 was monomerized as described before (30,31). Briefly, Aβ42 was dissolved in 98% formic acid.…”
Section: Methodsmentioning
confidence: 99%
“…In brief, PBS was used as running buffer at 25°C. Monomerized Aβ42 peptide was dissolved in 0.12% ammonia to 1 mg∕mL, diluted 1∶10 with 10 mM sodium acetate (pH 3.4), and subsequently immobilized to the sensor chip surface by amine coupling (30,31). Compounds were diluted from DMSO stock solutions in running buffer and injected for at least 1 min at a flow rate of 30 μL∕ min using the KINJECT command.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is possible that kinetics control the early intermediates, which form metastable structures that are stabilized when larger aggregates are formed. Experimentally, it has recently been suggested that engineered dimeric Alzheimer's ␤ (A␤) peptides significantly promote the growth of ␤-sheet fibrils (22). Furthermore, Walsh et al (23) have shown a potential synaptotoxicity of the A␤ dimer in vivo.…”
mentioning
confidence: 99%